2019
DOI: 10.1038/s41598-019-39791-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Streptococcus pneumoniae by a real-time PCR assay targeting SP2020

Abstract: Real-time PCR targeting lytA (the major autolysin gene) and piaB (permease gene of the pia ABC transporter) are currently used as the gold-standard culture-independent assays for Streptococcus pneumoniae identification. We evaluated the performance of a new real-time PCR assay – targeting SP2020 (putative transcriptional regulator gene) – and compared its performance with the assays previously described. A collection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 49 publications
1
62
2
1
Order By: Relevance
“…The proposition of using more than one marker is based on the findings that not all of the proposed species unique gene markers for S. pseudopneumoniae were present in all the strains tested. This is also supported by previous findings that markers reported to be unique for S. pneumoniae are also found in clinical isolates of other species of the Mitis-Group of the genus Streptococcus (Tavares et al, 2019). These facts further demonstrate the importance of using multi-locus approaches for identifications and differentiation of S. pneumoniae and S. pseudopneumoniae.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The proposition of using more than one marker is based on the findings that not all of the proposed species unique gene markers for S. pseudopneumoniae were present in all the strains tested. This is also supported by previous findings that markers reported to be unique for S. pneumoniae are also found in clinical isolates of other species of the Mitis-Group of the genus Streptococcus (Tavares et al, 2019). These facts further demonstrate the importance of using multi-locus approaches for identifications and differentiation of S. pneumoniae and S. pseudopneumoniae.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, other, previously reported gene markers for S. pneumoniae were not necessarily detected by our pangenomic approach. For instance, Tavares et al (2019) indicated that "lytA, piaB, and SP2020 were found in non-pneumococcal strains." Also, Carvalho et al (2007) reported that a psaAbased real-time PCR-assay was positive in S. pseudopneumoniae strains.…”
Section: Discussionmentioning
confidence: 99%
“…Two genes, piaA and piaB encoding components of an ABC transport system essential for iron uptake, were described as specific for S. pneumoniae but these genes are absent in some pneumococcal isolates, which limits the sensitivity of the test [79][80][81]. Moreover, piaA was detected in some S. mitis and S. pseudopneumoniae [66] and recently S. pseudopneumoniae isolates positive for piaB have been reported [70].…”
Section: Pcr-based Methods Of Identificationmentioning
confidence: 99%
“…Comparative genomic analyses of S. pneumoniae and S. pseudopneumoniae led to the identification of markers specific for these two species, respectively SPN0001/SP2020, encoding a GtnR-family transcriptional regulator, and SPS0002, specifying an osmosensitive potassium channel histidine kinase/response regulator KdpDE [88]. The specificity of both markers was close to 100%, with SPN0001/SP2020 found in a few non-pneumococcal strains and SPS0002 occasionally present in S. pneumoniae [70,88].…”
Section: Pcr-based Methods Of Identificationmentioning
confidence: 99%
“…Recently, new strategies to detect pneumococcal carriage based on real-time PCR (qPCR) have been proposed, validated, and are now being increasingly used [19][20][21][22][23] . The use of qPCR enables high sensitivity in samples where pneumococci are at low density.…”
Section: Re-evaluation Of Streptococcus Pneumoniae Carriage In Portugmentioning
confidence: 99%